Estimating Willingness to Pay for Improvements in Mobile Services - Dağlı, Orhan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The prominent approach for estimating people’s willingness to pay (WTP) for goods or services not currently in the market is the stated preference approach. Two methods of measuring stated WTP are contingent valuation method and choice experiments. We employ both methods in order to estimate consumers’ valuation of improvements in mobile services, focusing on 4G upgrades and roaming services. The contingent valuation method is performed in the payment ladder format, in order to estimate a nominal WTP for 4G. The choice experiment splits up the “mobile service improvement” into attributes, and investigates the preferences for these individual attributes: increased mobile internet speed (possible with 4G), unlimited mobile internet use, improved quality (possible with 4G) and unrestrained use in two neighbouring countries (unrestrained roaming). We collect the data for the study through a face-to-face survey held in all districts of North Cyprus. The results indicate that people value unrestrained roaming services the most. Increased speed and unlimited use attributes are next, and are similarly significant at the 1% level. The impact of improved quality is statistically insignificant at the 5% level, suggesting that consumers are content with the current level of quality they receive with 3G. We conclude that bilateral roaming regulation between governments is more valuable than 4G investments. Keywords: Mobile telecommunication services, Choice experiment, Willingness to pay, 4G, Roaming.

ÖZ : Hâlihazırda pazarda olmayan ürün veya hizmetler için halkın ödeme istekliliğini (Öİ) tespit etmek adına kullanılan başlıca yaklaşım bahsedilen tercih yaklaşımıdır. Bahsedilen Öİ değerini ölçmenin iki yöntemi olası değerlendirme yöntemi ve seçim deneyleridir. Bu çalışmada tüketicilerin mobil hizmetlerdeki (4G ve dolaşım odaklı) iyileştirmelere biçtiği ekonomik değeri ölçmek için iki yöntemi de kullandık. Olası değerlendirme yöntemi ödeme merdiveni formatında, 4G için ödeme istekliliği değerini tespit etmek adına uygulanmıştır. Seçim deneyi yöntemi mobil hizmet iyileştirmesini parçalarına ayırıp bu parçalar ile ilgili tercihleri tespit etmek amaçlı kullanılmıştır. Bu parçalar mobil internet hızında artış (4G ile mümkün), sınırsız mobil internet kullanımı, iyileşmiş kalite (4G ile mümkün) ve iki komşu ülkede engelsiz kullanımdır (engelsiz dolaşım). Çalışmada kullanılan veri Kuzey Kıbrıs’ın tüm ilçelerinde, yüz yüze mülakat yöntemi ile yapılan bir anket ile elde edilmiştir. Sonuçlar insanların en fazla engelsiz dolaşım hizmetlerine değer verdiğini göstermektedir. Ardından sırasıyla internet hızında artış ve sınırsız kullanım gelmektedir, ve bu iki özelliğin etkileri %1 derecesinde anlamlıdır. İyileştirilmiş kalitenin etkisi %5 derecesinde anlamsızdır, bu da tüketicilerin 3G ile sahip oldukları mevcut kalite seviyesinden memnun olduğunu göstermektedir. Buradan da çift taraflı dolaşım düzenlemelerinin 4G yatırımlarından daha değerli olduğu sonucuna varıyoruz. Anahtar kelimeler: Mobil telekomünikasyon hizmetleri, Seçim deneyi, Ödeme İstekliliği, 4G, Roaming.
Doctor of Philosophy in Economics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2016. Supervisor: Prof. Dr. Glenn P. Jenkins.
Keywords: Economics; Willingness to pay - Mobile Services; Mobile telecommunication services; Choice experiment; Willingness to pay; 4G; Roaming